The Role Of Language In Shaping National Identity: A Comparative Study Of Indonesia, Kazakhstan, and Monaco - Fatimatul Labibah; Aji Surakhmat (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This paper explores the significant role of language in the construction and expression of national identity in three distinct countries: Indonesia, Kazakhstan, and Monaco. By analyzing national languages, official discourse, and the cultural narratives embedded within them, the study aims to highlight the ways in which language policies reflect and reinforce the cultural and political aspirations of these nations. A comparison of language practices will reveal the dynamics of language as a cultural tool for nation-building in diverse sociopolitical contexts.